Phytoextraction of copper by cicerarientum - SWARNA SHIKHA; PAMMI GAUBA (International Journal of Pharma and Bio Sciences, 2016)
Environmental pollution is a global problem that affects both the developing and developed countries. To an equal extent both human and natural processes contribute to environmental pollution. The contaminants are can be either organic or inorganic. The aim of this study was to find the remediation potential of Cicer arientum against different concentration of Copper in hydroponics culture at germination and postgermination stage and It was seen that the percentage of remediation after third week is around 78.63% which is approximately twice of 38.4 % that was observed in first week. Impact of toxicity was also observed in plant height and chlorophyll content.